2017
DOI: 10.20959/wjpps201705-9153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activity of Ethanol Leaf Extracts of Psidium Guajava Linn. Against Clinical Isolates From Wound Infections

Abstract: ABSTRACT50mg/ml, 100mg/ml, 150mg/ml, 200mg/ml and 250 mg/ml. Maximum inhibition was observed at a concentration of 250mg/ml of the crude ethanol leaf extract of Psidium guajava L. The study suggests that ethanolic leaf extracts of Psidium guajava L. can be used as a potential candidate to treat bacterial wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The The results revealed that the culture filtrate of Streptomyces species effectively scavenged DPP and ABTS radicals in a concentration dependent manner when compared with the IC50 values [17,21]. Production of protease from the strain of streptomyces was simple and it will be easy to scale up, as this actinobacteria grows on simple media with feathers as a sole source of carbon, nitrogen, and energy, thus allowing its enzyme production from an inexpensive substrate and a commercial potential with low productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The The results revealed that the culture filtrate of Streptomyces species effectively scavenged DPP and ABTS radicals in a concentration dependent manner when compared with the IC50 values [17,21]. Production of protease from the strain of streptomyces was simple and it will be easy to scale up, as this actinobacteria grows on simple media with feathers as a sole source of carbon, nitrogen, and energy, thus allowing its enzyme production from an inexpensive substrate and a commercial potential with low productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, an antimicrobial effect of allspice EO was also reported against S. aureus and E. coli (Oussalah et al, 2006;Oussalah et al, 2007;Lowe et al, 2017;Asha et al, 2013), S. typhi, and P. aeruginosa (Kumar et al, 2010) and S. typhimurium and P. putida (Oussalah et al, 2006;Oussalah et al, 2007).…”
Section: Antimicrobial Assaymentioning
confidence: 92%